The relationship between the athletic burnout and type of passion for physical activity in students based on the dualistic model of passion - Milad Esmaeili HeidarAbad; Mahmoud Sheikh; Fahimeh Hassani; Arefeh Esmaeili (مجله علوم روانشناختی, 2017)
Participation in regular physical activity is essential for promoting mental and physical well-being. Researchers find that one of the reasons for withdraw from physical activity is burnout, which is the result of stress resulting in severe physical needs, psychological and emotional arise. To predict burnout, the issue is whether the passion to physical activity can play a role on it?  So, the aim of this study was to investigate the relationship between type of passion and athletic burnout in the physical education students of Tehran University. The study population was composed of all students at Tehran University, which 173 volunteer completed questionnaires. The research method was correlation. The instruments used included a demographic questionnaire, Passion Scale of Vallerand et all (2011) and athletic burnout questionnaire (ABQ) Raedek and Smith (2003). In this study, according to the normal distribution of data, the Pearson correlation coefficient was used to analyze the data at a significance level of P≤0/05. The results showed that obsessive passion has significant relationship with all subscales of athlete burnout (with emotional and physical exhaustion 0/50, with reduced sense of accomplishment 0/23, and with Devaluation 0/26). On the other hand, there are no significant relation between harmonious passion with dimensions of burnout. According to the results, athletes who have obsessive passion about their activities are more likely to experience an athletic burnout, and there are few possibilities for athletes with harmonious enthusiasm to experience burnout.